In-vivo antimalarial activity of the endophytic actinobacterium, Streptomyces SUK 10 - Baba, Mohd Shukri; Mohamad Zin, Noraziah; Abu Hassan, Zainal Abidin; Latip, Jalifah; Pethick, Florence; Hunter, Iain S.; Edrada-Ebel, RuAngelie; Herron, Paul R. (The Microbiological Society of Korea, 2015)
Endophytic bacteria, such as Streptomyces, have the potential to act as a source for novel bioactive molecules with medicinal properties. The present study was aimed at assessing the antimalarial activity of crude extract isolated from various strains of actinobacteria living endophytically in some Malaysian medicinal plants. Using the four day suppression test method on male ICR strain mice, compounds produced from three strains of Streptomyces (SUK8, SUK10, and SUK27) were tested in vivo against Plasmodium berghei PZZ1/100 in an antimalarial screen using crude extracts at four different concentrations. One of these extracts, isolated from Streptomyces SUK10 obtained from the bark of Shorea ovalis tree, showed inhibition of the test organism and was further tested against P. berghei-infected mice for antimalarial activity at different concentrations. There was a positive relationship between the survival of the infected mouse group treated with 50 μg/kg body weight (bw) of ethyl acetate-SUK10 crude extract and the ability to inhibit the parasites growth. The parasite inhibition percentage for this group showed that 50% of the mice survived for more than 90 days after infection with the parasite. The nucleotide sequence and phylogenetic tree suggested that Streptomyces SUK10 may constitute a new species within the Streptomyces genus. As part of the drug discovery process, these promising finding may contribute to the medicinal and pharmaceutical field for malarial treatment.